Decomposition of biospeckle images in temporary spectral bands - Sendra, Gonzalo Hernán (2005)
We present a method of analysis of images of dynamic speckle based on the filtering in frequency bands of the temporary history of each pixel. Butterworth filters are applied to the temporary evolution, and different images are constructed showing the energy in each frequency band. Different degrees of activity of the sample in study, presumably attributed to different origins, are found. The method is exemplified with images of bruising damage in fruits and of biological activity in germinating corn seeds. It is found that the activity in the bruised region of an apple differs from the activity of healthy regions in a certain characteristic frequency range. The activity of the embryo can also be distinguished from that of the endosperm in corn seeds during germination.